On the Biological Standard of Living of Eighteenth-Century Americans: Taller, Richer, Healthier - John Komlos (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2003)
This study analyses the physical stature of runaway apprentices and military deserters based on advertisements collected from 18th-century newspapers, in order to explore the biological welfare of colonial and early-national Americans. The results indicate that heights declined somewhat at mid-century, but increased substantially thereafter. The findings are generally in keeping with trends in mortality and in economic activity. The Americans were much taller than Europeans: by the 1780s adults were as much as 6.6 cm taller than Englishmen, and at age 16 American apprentices were some 12 cm taller than the poor children of London.
urn:nbn:de:bvb:19-epub-53-0
Keywords: N11; I31; I12; N31; 330; Anthropometrics; Living Standards; 18th century; colonial US